The New Diffusion Tensor and the Equatorial Anomaly Altitudes of F-Region - Yeşil, Ali; Sağır, Selcuk (My University, 2017)
In this study, the difference (?D = D(??0)- D(?=0)) of the classical diffusion tensor (D0, D1, D for both steady-state and unsteady-case) for F- region of the ionosphere at the equatorial region is investigated by taking (B=B0z), the geometry of the Earth's magnetic field and by neglecting the neutral winds velocity (U). The measurements were made in the height (280,300,340,390 and 410 km) where the equatorial anomaly was observed predominantly. The magnitudes of the difference of classical diffusion tensor for electrons are ?D0>?D1 >?D2 for all seasons with respect to both 12.00LT and 24.00LT at F-region. However, ?D1 and ?D2 are bigger during nighttime than daytime and show a behavior reverse to the change with latitude of electron density in the magnetic equator. It is possible to say that the behavior of them can be the result of electromagnetic drift and dynamo effect.
Keywords: Fizik; Uygulamalı; Fizik; Partiküller ve Alanlar